THEORY AND PRACTICE OF REGIONAL ECONOMIC INTEGRATIONS - Popović, Goran (Economics of Agriculture, 2010)
Regional economic integrations are the fundament on which modern economic relations are based. They stem out of numerous interests of those countries whose desire is to transfer some part of their authority into a new national-legal framework. One of the decisive reasons for these changes is the economic interest. It is realized because by integrating singular economic markets, better economic effects are achieved for all members of the integration. These effects are achieved for better exploitation of natural resources, workforce, etc. Knowledge, technological development and other positive externalities are used within these integrations. For this reason the integrations are more and more present in modern socio-economic activities. They are based on relevant theoretical works which have in the past half a century provided the scientific confirmation of the existence of great economic benefits gained through these integrations. Theory wise, each integration brings changes to the consumers and manufacturers of a country that enters it, while other changes take place as well. The most notable authors of the theories of customs union, economic and other integrations are Viner, Meade, Balassa, Lipsey and others. The EU is a typical example of a great and successful integration. It is still being enlarged. The new member states achieve faster growth through the advantages provided by the large market. The European Union has a rich history of its development while the ideas of European integrations are century-or even millennium-old ideas.